REVIEW ARTICLE ON PROSPECTIVE ANALYSIS OF PRISCRIPTION PATTERN OF ANTIMICROBIAL THERAPY FOR URINARY TRACT INFECTION IN PREGNANT FEMALE PATIENT - Shikha Pal; Narendra Kumar Yadav; Aayush Yadav; Mandeep, Mahipal (Journal of Biomedical and Pharmaceutical Research, 2020)
Urinary tract infection (UTI) are common during pregnancy. These most common causative organism is E.coli.1 A urinary tract infection (UTI) is an infection in any part of urinary system including kidney, ureters, bladder and urethra.2 The urinary can be divided into the upper urinary tract and the lower urinary tract. The upper urinary tract consist of the kidney and ureters and lower urinary tract consist of the bladder and the urethra.2 UTI can be classified by anatomic site of involvement into lower and upper urinary tract infection.3 Asymptomatic bacteriuria can lead to the development of cystitis and pyelonephritis. All pregnant women should be screened for bacteriuria and subsequently treated with antibiotics such as Nitrofurantoin, sulfisoxazole,or cephalexin. can be life threatening illness, with the increased risk of Perinatal and Neonatal mobility. Pregnant women with urinary group B Streptococcal infection should be treated and should receive intrapartum prophylactic therapy.